Advances in the Economics of Religion - Carvalho, Jean-Paul; Iyer, Sriya; Rubin, Jared ca. 20./21. Jh. (International Economic Association Series, 2019)
1. Introduction (Jean-Paul Carvalho, Sriya Iyer, and Jared Rubin) -- Part I: Theoretical Advances in the Economics of Religion -- 2. Religious Clubs: The Strategic Role of Religious Identity (Jean-Paul Carvalho) -- 3. Spatial Models of Religious Market Competition: A Critical Assessment (Michael McBride) -- 4. When Average is Irrelevant: Computational Modeling of Religious Groups (Michael D. Makowsky) -- 5. The Intelligent Design of Religious Beliefs (Gilat Levy) -- 6. Religion and Segregation (Ronny Razin) -- 7. Religious and Cultural Leaders (Anja Prummer) -- 8. Intermediated Social Preferences: Altruism in an Algorithmic Era (Daniel L. Chen) -- Part II: Empirical Advances in the Economics of Religion -- 9. Religion and Demography (Sriya Iyer) -- 10. Economics and Church State Research: Past, Present, Future (Dan Hungerman and Timothy Weninger) -- 11. Protestants and Catholics and Educational Investment in Guatemala (Rachel M. McCleary and Robert J. Barro) -- 12. The Religious Factor in Private Education in the United States (Danny Cohen-Zada and Moshe Justman) -- 13. How Luther’s Quest for Education Changed German Economic History: 9+5 Theses on the Effects of the Protestant Reformation (Sascha O. Becker and Ludger Woessmann) -- 14. Hindu-Muslim Violence in India: A Postscript From the 21st Century (Anirban Mitra and Debraj Ray) -- 15. Religion and Conflict: A Quantitative Approach (José G. Montalvo and Marta Reynal-Querol) -- 16. Why are Some Societies More Religious than Others? (Jeanet Sinding Bentzen) -- 17. Socioeconomic Inequality across Religious Groups: Self-Selection or Religion-Induced Human Capital Accumulation? The Case of Egypt (Mohamed Saleh) -- 18. Religion and the European Union (Benito Arruñada and Matthias Krapf) -- Part III: Advances in Religion and Political Economy -- 19. The Political and Economic Consequences of Religious Legitimacy (Jared Rubin) -- 20. Religious Legitimacy and the Joint Evolution of Culture and Institutions (Alberto Bisin, Avner Seror, and Thierry Verdier) -- 21. Strategic Interactions between Religion and Politics: the Case of Islam (Jean-Philippe Platteau) -- 22. State and Religion: An Economic Approach (Metin M. Coşgel and Thomas J. Miceli) -- 23. A Great Academic Re-Awakening: The Return to a Political Economy of Religion (Anthony Gill) -- 24. The State, Toleration, and Religious Freedom (Noel Johnson and Mark Koyama) -- 25. Religiosity and Economic Performance: The Role of Personal Liberties (Laura Mayoral and Joan Esteban) -- 26. Causes and Consequences of Monotheism in the Supply of Religion (Murat Iyigun) -- 27. Religion, Political Power and Human Capital Formation: Evidence from Islamic History (Eric Chaney) -- 28. Islam, Trade, and Innovation (Alireza Naghavi)